Paediatric Nutrition (MDPI - Multidisciplinary Digital Publishing Institute, 2014)
Food and nutrition has been central to human culture, philosophy and science since the beginning of civilisation. However the building blocks of food and nutrition, the nutrients, remained unknown until the late 19th century. Over the next 100 years advances in physics, chemistry and physiology led to rapid developments in our knowledge, first with development of an understanding of energy and the macronutrients, followed by the minerals and vitamins. The first vitamins to be explored scientifically were thiamine, vitamin D and C and in 1935 ascorbic acid was synthesised, beginning the 20th century rapid development of knowledge of nutrients[1]. [...]